Sharing Isn’t Easy: Food Waste and Food Redistribution in Maine K–12 Schools - Berry, Brieanne; Acheson, Ann (Maine Policy Review, 2017)
Approximately 30 percent of food in the United States is wasted. When food is landfilled instead of eaten, the economic and natural resources used to produce and transport that food are also wasted. At the same time, however, food insecurity remains a pressing issue both in the United States and within the state of Maine. This paper explores efforts to reduce food waste and address food insecurity in Maine’s K–12 school system, with an emphasis on food redistribution. Research indicates that schools produce substantial amounts of food waste, but little is known about strategies that schools employ to address food waste, either through formal policy or grassroots efforts. Based on an analysis of school board waste policies and interviews with school officials in Maine, this study suggests that the adoption of specific types of practices to reduce food waste is influenced by multiple factors.